1988
DOI: 10.1002/art.1790010203
|View full text |Cite
|
Sign up to set email alerts
|

Social support and psychosocial adjustment to rheumatoid arthritis quantitative and qualitative findings

Abstract: One hundred twenty‐nine individuals with rheumatoid arthritis were interviewed, and their satisfaction with several aspects of social support was rated. Quantitative analyses showed that patients' overall support satisfaction was related to health care providers' ratings of their psychosocial adjustment, independent of patients' demographic characteristics, illness duration, disease activity, and functional disability. Furthermore, the relation between support satisfaction and psychosocial adjustment increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 20 publications
4
41
0
4
Order By: Relevance
“…The present findings support the buffering model. Findings in other studies have been similar (Affleck, Pfeiffer, Tennen, & Fifield, 1988;Warren et al, 1996;Wasley & Lox, 1998). These findings draw attention to the importance of the type of injury in mood state and in life satisfaction.…”
Section: Discussionsupporting
confidence: 77%
“…The present findings support the buffering model. Findings in other studies have been similar (Affleck, Pfeiffer, Tennen, & Fifield, 1988;Warren et al, 1996;Wasley & Lox, 1998). These findings draw attention to the importance of the type of injury in mood state and in life satisfaction.…”
Section: Discussionsupporting
confidence: 77%
“…In research with RA patients, Smith and Wallston (42), using a comprehensive set of +year longitudinal data on health, social support, and coping, found that a lack of emotional support was an antecedent of poorer psychosocial adjustment. These findings corroborated previous research on social support and depressive symptoms in RA (44)(45)(46). In a similar vein, Fitzpatrick and colleagues (13) reportecl a hierarchical regression in which social isolation, after controlling for sociodemographics and disease severity, contributed 4% to the explanation of differences in depressed mood and was also predictive of individual differences in the self-esteem of RA patients.…”
Section: Introductionsupporting
confidence: 87%
“…family and friends can also play a significant role in the adaptation to the disease. Significant relationships have been found between social support and health status in arthritis patients (Affleck et al, 1988;Weinberger et al, 1990;Goodenow et al, 1990).…”
Section: (3) Mediating Psychosocial Factorsmentioning
confidence: 99%